Fetal macrosomia as a complication of gestational diabetes and the effectiveness of diet and physical exercise as primary treatment: Literature review (Research, Society and Development, 2023)
Gestational diabetes mellitus (GDM) is a metabolic disorder characterized by elevated blood glucose levels during pregnancy, with fetal macrosomia (FM) being the most prevalent complication, resulting in birth complications such as perineal trauma and emergency cesarean section. This study aims to analyze the main complications of GDM, associated risk factors, and consequences for the health of the mother and fetus, focusing on diet and physical exercise as primary treatment. The review included studies published between 2006 and 2022, selected from the PubMed, SciELO, Google Scholar, and BVS databases. It is evident that diet and physical exercise are effective in controlling GDM and can be used as initial treatment. However, in some cases, the use of hypoglycemic medications may be necessary. Therefore, diet and physical activity are essential in the treatment of GDM, but an individualized approach may require pharmacological interventions.